An observational study of pet feeding practices and how these have changed between 2008 and 2018. (18th June 2020) - Dodd, Sarah; Cave, Nick; Abood, Sarah; Shoveller, Anna‐Kate; Adolphe, Jennifer; Verbrugghe, Adronie
Abstract : Background: Pet owners have many feeding options, some may be considered unconventional by veterinary practitioners. Provision of appropriate nutrition is a basic requirement, with adverse health outcomes possible when a pet diet is inadequate. Objective: To capture dog and cat feeding practices, with a special focus on countries with large English‐speaking populations, and to compare with data published over the previous 10 years. Methods: An electronic questionnaire was provided for dog and cat owners online. Responses were analysed using descriptive statistics, and comparisons made with data from nine peer‐reviewed articles published over the previous 10 years. Results: Responses from 3673 English‐speaking dog and cat owners in Australia, Canada, New Zealand, the UK and the USA were included. In previous publications, conventional (commercial, heat‐processed) products were the predominant method of feeding. In recent publications, feeding unconventional (raw, homemade, vegetarian) diets appeared more prevalent. In the present study, most (79 per cent dogs, 90 per cent cats) pets were offered conventional food. However a few (13 per cent dogs, 32 per cent cats) pets were fed conventional foods exclusively. Many pets were offered homemade (64 per cent dogs, 46 per cent cats) and/or raw (66 per cent dogs, 53 per cent cats) foods. Different feeding practices were associated with geographical location. Conclusion: As an increased risk of nutrient insufficiency and associated conditions have been attributed to unconventional feeding practices, veterinarians must be aware of pet feeding trends and educate clients about the nutritional needs of companion animals.